(5.6x+2)(5.6x-2)=

Simple and best practice solution for (5.6x+2)(5.6x-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5.6x+2)(5.6x-2)= equation:


Simplifying
(5.6x + 2)(5.6x + -2) = 0

Reorder the terms:
(2 + 5.6x)(5.6x + -2) = 0

Reorder the terms:
(2 + 5.6x)(-2 + 5.6x) = 0

Multiply (2 + 5.6x) * (-2 + 5.6x)
(2(-2 + 5.6x) + 5.6x * (-2 + 5.6x)) = 0
((-2 * 2 + 5.6x * 2) + 5.6x * (-2 + 5.6x)) = 0
((-4 + 11.2x) + 5.6x * (-2 + 5.6x)) = 0
(-4 + 11.2x + (-2 * 5.6x + 5.6x * 5.6x)) = 0
(-4 + 11.2x + (-11.2x + 31.36x2)) = 0

Combine like terms: 11.2x + -11.2x = 0.0
(-4 + 0.0 + 31.36x2) = 0
(-4 + 31.36x2) = 0

Solving
-4 + 31.36x2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 31.36x2 = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 31.36x2 = 0 + 4
31.36x2 = 0 + 4

Combine like terms: 0 + 4 = 4
31.36x2 = 4

Divide each side by '31.36'.
x2 = 0.1275510204

Simplifying
x2 = 0.1275510204

Take the square root of each side:
x = {-0.357142857, 0.357142857}

See similar equations:

| 25x^2+9y^2-18y-216=0 | | (0.6x-1.28)(18x+8)= | | 72=4x-12 | | 2m(n+3)-m(2n+1)= | | 2e^x/8e^-x | | X+0.6x=250y | | -5x+10=14+(4+x) | | g+7f=16 | | 12=3*x | | 4x^2+x=44 | | 9x+-9y=27 | | f(x)=10x-18 | | 4x^2+x-44=0 | | 50-(30+80)= | | u-v+6u-3v= | | (3x-4)(x-20)=3x(x-9)-3 | | 2-3(7x+9)=6 | | 5n^2+n-5=0 | | N+4=3n+16 | | -5t^2+40t+20= | | 0.2r-1.3r+0.6=-0.9+3.6 | | 19/2/3 | | 2/3/18 | | 2k+2=-13+3k | | X+0.6x+0.03x=500 | | 1/5-1/6z=7/6 | | N-9=9+15 | | 4(3z+5)=10-2(z-5) | | 121^-1/2 | | 426=350t | | 2(1-7y)=4y+3 | | T-5+7+2k-3k=k-8 |

Equations solver categories